Pachamama - Mutter Erde : O. René Chacón, Renate Gehrcke, Raquel Hofer, Wolfgang Hunecke, Fernando de la Jara, Jürgen Luff, Mirtha Monge de Steinhöfel, Ana Uribe : Ausstellung. (Heidelberg : Universität, 1992)
O. René Chacón ; Renate Gehrcke ; Raquel Hofer ; Wolfgang Hunecke ; Fernando de la Jara ; Jürgen Luff ; Mirtha Monge de Steinhöfel ; Ana Uribe
Pachamama - Mutter Erde, Universität, Heidelberg, Mai 1992
boek